Comparison of production parameters, gut histology, organ weights, and portion yields of broilers supplemented with Ateli plus - Teuchert, Nicole (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScAgric)--Stellenbosch University, 2014.